Unveiling the Role of BODIPY Dyes as Small-Molecule Hole Transport Material in Inverted Planar Perovskite Solar Cells - Seoneray, Isabel; Wu, Jianchang; Rocha-Ortiz, Juan S.; Bornschlegl, Andreas; Barabash, Anastasia; Wang, Yunuo; Lüer, Larry; Hauch, Jens; García, Angélica; Zapata-Rivera, Jhon; Brabec, Christoph J.; Ortiz, Alejandro (Solar RRL, 2024)
Perovskite solar cells (PSCs) have become a research hotspot since their dramatic increase in power conversion efficiency (PCE), surpassing 26% due to advances in cell engineering and interfacial layers. Within the last factor, hole transporting materials play a crucial role in enhancing device performance and stability. Among several molecular building blocks, BODIPYs are attractive for the design of novel hole transporting material (HTMs) due to their outstanding photophysical and charge transport properties easily tuned by synthetic modifications. Herein, the synthesis of five new BODIPY-based HTMs PyBDP 1–5 are reported, functionalized at the meso- and α- positions with pyrenyl and arylamino units, respectively. The resulting compounds exhibit broad absorption in the visible region, remarkable thermal stability, narrow bandgaps, suitable energy levels, and good hole extraction capability, as subtracted from experimental and computational characterizations. The performance of the BODIPY derivatives as HTMs is evaluated in planar inverted (p-i-n) PSCs and compared to commonly used PTAA, resulting in highly efficient systems, reaching PCEs very close to that obtained with the reference polymer (21.51%). The incorporation of these BODIPY-based HTMs result in an outstanding PCE of 20.37% for devices including PyBDP-1 and 19.97% for devises containing PyBDP-3, thus demonstrating that BODIPY derivatives are a promising alternative to obtain simple and efficient organic HTMs.
CRIS-Team Scopus Importer:2024-05-31
Keywords: arylamine; BODIPY; hole-transporting material; perovskite solar cells; pyrene